Landmark Point-Based Mobile Robot System with IoT Communication for Warehouse Environments - Saragih, Intan; Herwian, Eduardus Arjuna; Mariel, Reinald; Syiraz, Rifqi Fathin; Fuadi, Azam Zamhuri; Rusdinar, Angga (eProceedings of Engineering, 2022)
This paper presents a mobile robot system for automated warehouse tasks, utilizing magnetic landmark points for precise navigation and Internet of Things (IoT) communication for efficient data exchange. A 16-element magnetic sensor guides the robot, with central elements detecting the path and outer elements identifying special markers that trigger actions like stopping, charging, or direction changes. An intelligent stopping system allows the robot to skip locations without stop commands. A central cloud-based communication setup, using Google Sheets, enables secure and efficient two-way data exchange between the operator and the robot via HTTPS/TLS and JSON formats. Experimental results show an average success rate of 91.42% for marker detection, with performance variations influenced by speed and marker placement accuracy. The study also analyzes end-to-end communication latency and throughput, highlighting areas for future optimization for real-time capabilities. Keywords—Mobile robot, Landmark point, IoT communication, Cloud robotics, Warehouse automation, Magnetic guidance, Data exchange, Latency, Throughput